2019
DOI: 10.1002/joa3.12188
|View full text |Cite
|
Sign up to set email alerts
|

Association between PR Interval, First‐degree atrioventricular block and major arrhythmic events in patients with Brugada syndrome – Systematic review and meta‐analysis

Abstract: Background Risk stratification in patients with asymptomatic Brugada Syndrome is challenging, and despite recent advances, there is no clear evidence. The first‐degree atrioventricular block was hypothesized to be a predictor of arrhythmic events. Measurement of the PR interval and diagnosing atrioventricular block from surface ECG is easy, noninvasive, and cost‐effective. We aimed to assess the latest evidence on PR interval or first‐degree atrioventricular block and major arrhythmic events related to Brugada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…Recently, our study group, for the first time, demonstrated that first-AV block was an independent predictor of malignant arrhythmic events (18). A more recent meta-analysis by Pranata et al confirms that first-degree AV block is associated with more frequent major arrhythmic events in BrS patients (41). In the present study, we found that among ECG abnormalities, patients who experienced malignant arrhythmic events after GR had more often conduction abnormalities including first-degree AV block at baseline (P = 0.04).…”
Section: Conduction Abnormalities In Brugada Syndromesupporting
confidence: 53%
“…Recently, our study group, for the first time, demonstrated that first-AV block was an independent predictor of malignant arrhythmic events (18). A more recent meta-analysis by Pranata et al confirms that first-degree AV block is associated with more frequent major arrhythmic events in BrS patients (41). In the present study, we found that among ECG abnormalities, patients who experienced malignant arrhythmic events after GR had more often conduction abnormalities including first-degree AV block at baseline (P = 0.04).…”
Section: Conduction Abnormalities In Brugada Syndromesupporting
confidence: 53%
“…For example, excess outflow of potassium current during early repolarization or reduced inward current via calcium channels may contribute to BrS pathophysiology [ 21 ]. The reduced inward current flow of sodium in BrS patients may result in prolonged PR (PQ) interval, first degree atrioventricular block [ 22 ], slow cardiac conduction (intraventricular and His–Purkinje), phase 2 reentry and premature repolarization [ 21 ], low-amplitude and high-frequency electrical activity in RVOT epicardium (late potentials), and ventricular arrhythmias [ 12 , 23 ].…”
Section: Pathogenesis Of Brsmentioning
confidence: 99%
“… Overview of pathomechanisms involved in Brugada syndrome [ 9 , 10 , 11 , 12 , 21 , 22 , 24 , 25 , 26 , 27 ]. Abbreviations: AT—antithrombin; BrS—Brugada syndrome; Ca 2+ —calcium; ECG—electrocardiogram; K + —potassium; ICD—implantable cardioverter–defibrillator; Na + —sodium; SCD—sudden cardiac death; SCN5A—sodium voltage-gated channel alpha subunit 5; RV—right ventricle; RVOT—right ventricular outflow tract; VF—ventricular fibrillation; VT—ventricular tachycardia.…”
Section: Figurementioning
confidence: 99%
“…Hence, several studies investigated the association between several ECG markers and major arrhythmic events (MAE) in BrS patients to predict the likelihood of SCD and VTA events. Several meta-analyses revealed that first-degree atrioventricular block, fragmented QRS, wide QRS complex, early repolarization, especially in the inferolateral region, atrial fibrillation, Tpeak-Tend dispersion, Tpeak-Tend interval, and (Tpeak-Tend)/QTc ratio were significantly associated with a higher risk of MAE in BrS patients (8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%